A Thermogravimetric study of the characteristics of pyrolysis of cellulose isolated from selected biomass. (15th June 2018) - Zhang, Zhezi; Zhu, Mingming; Zhang, Dongke
Highlights: Pyrolysis characteristics of cellulose from various biomass resources was studied. Isolated and reference celluloses showed similar chemical structure. Isolated and reference celluloses showed different crystallinity, crystallite size. Structural differences of cellulose strongly affected their pyrolysis behavior. Abstract: Utilisation of biomass by means of pyrolysis is of practical interest for the production and use of biofuels at small and flexible scales. Biomass consists of three major components, namely, cellulose, hemicellulose and lignin and their contents vary from feedstock to feedstock. Understanding the pyrolysis behaviour of each component and their interactions holds a key to understanding the complex biomass pyrolysis process. This study was aimed to compare the pyrolysis characteristics of cellulose from various biomass resources, namely pine wood, poplar wood and wheat straw, and pure cellulose samples acquired from Sigma Aldrich and Avicel. Cellulose samples were isolated from the raw biomass samples using a well-established cellulose isolation technique. Fourier transform infrared spectroscopy (FTIR), X-ray diffractometer (XRD) and scanning electron microscope (SEM) were applied to characterise the surface functional groups, the crystallinity and the morphologies of the samples. The pyrolysis experiments were performed using a thermogravimetric analyser (TGA) in nitrogen at 10 K min −1 heating rate from room temperature to the final temperature of 823 K. The FTIR, XRD and SEM results indicated that cellulose can be successfully isolated from the raw biomass samples via the chemical treatment used. The cellulose samples isolated from the selected biomass had lower crystallinity and smaller crystallite compared to the reference cellulose. The cellulose isolated from pine wood, poplar wood and wheat straw showed similar pyrolysis characteristics but differed significantly from the reference celluloses. The temperature corresponding to the maximum weight loss rate of the isolated cellulose samples was ca 5–18 K lower than that of the reference celluloses and exhibited a large flat shoulder in the temperature range of 475–575 K.